Flexible manufacturing systems decision support for design and operation - Tempelmeier, Horst 1952-; Kuhn, Heinrich 1959- (Wiley series in systems engineering, 1993)
Now, this comprehensive and systematic overview of both the design models and quantitative solution methods for FMS support, configuration, and operation rectifies that problem. Students, production managers/planners, and FMS installation planners can now find everything they need in one authoritative and up-to-date source